A 37-kilodalton glycoprotein from a baculovirus of Orgyia pseudotsugata is localized to cytoplasmic inclusion bodies. - Gross, C H (1993)
The gene encoding a 37-kDa glycoprotein (gp37) of Orgyia pseudotsugata multinucleocapsid nuclear polyhedrosis virus (OpMNPV) was located and sequenced. gp37 of OpMNPV was found to have 62 and 37% amino acid sequence identity with gp37 of Autographa californica multinucleocapsid nuclear polyhedrosis virus (AcMNPV) and with a protein reported to be a component of occlusion bodies from Choristoneura biennis entomopoxvirus, respectively. The mRNA start site of the OpMNPV gp37 gene was mapped within a late promoter sequence (TTAAG). A TrpE fusion protein containing 55% of the OpMNPV gp37 gene amino acid sequence was used to generate a monospecific antiserum. Western immunoblot analysis of OpMNPV-infected Lymantria dispar cells detected gp37 beginning at 24 h postinfection. Immunoelectron microscopy indicated that the protein is concentrated in cytoplasmic inclusion bodies late in infection. In contrast to gp37 of AcMNPV which was present in the matrix of occlusion bodies, OpMNPV gp37 was not observed in this location. Neither OpMNPV nor AcMNPV gp37 was associated with the polyhedron envelope.